2019
DOI: 10.3390/met9111164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milling Conditions on the Microstructural Design in Aluminum Based Alloy Fabricated by SPS

Abstract: In this work, aluminum-based alloys were mechanically alloyed by various doping elements followed by spark plasma sintering. Three different mixing methods were studied. First, all elemental powders were mixed for 24 h. In the second and the third method, powders were divided into three groups, and each group was milled separately for different times. Then the obtained mixtures were grouped together and again milled for 12 and 24 h, for the M2 and M3 mixtures, respectively. The influence of milling parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The friction coefficient for Al-Cr composition was two times lower and 12% less than for bronze and Al-Mo, respectively. These results support the conclusions claim that the value of friction coefficients is not a major criterion of materials wear resistance, which was reached in the previous study [48].…”
Section: Tribological Behavioursupporting
confidence: 92%
See 4 more Smart Citations
“…The friction coefficient for Al-Cr composition was two times lower and 12% less than for bronze and Al-Mo, respectively. These results support the conclusions claim that the value of friction coefficients is not a major criterion of materials wear resistance, which was reached in the previous study [48].…”
Section: Tribological Behavioursupporting
confidence: 92%
“…In our previous study, we had confirmed the effectiveness of the MA and spark plasma sintering method for the preparation of tailored mixtures of metallic powders, enabling microstructural characteristics that could be favorable for the formation of secondary structures on the tribosurfaces [48]. However, the evaluation of the mechanical and tribological behavior of the obtained compositions was not presented.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations